Experimental Study on Aerosol Natural Deposition under Accident Sequence Condition - LI Tao1, GU Haifeng1, WANG Hui1, 2, SUN Qingyang1, TANG Tianhao1, YU Jianqun1, HUANG Ningyuan1 (Yuanzineng kexue jishu)
When severe accident occurs, reactor core melts, then a large amount of radioactive substances are released into containment with steam and exist in the form of aerosol. Aerosol will naturally deposit in containment under the mechanism of gravity deposition and diffusiophoresis. As the severe accident sequence progresses, the thermal environment of the containment continues to change, and the emission characteristics of the aerosol, such as the release time and release rate, will also change, which brings great uncertainty to the deposition behavior of the aerosol in the containment vessel. In order to explore the natural deposition behavior characteristics of aerosols under the conditions of accident sequence in large-scale containment, the large-scale aerosol comprehensive behavior experimental bench was used to study the natural deposition behavior of aerosol under the condition of real accident, and the passive cooling system in the form of heat exchanger used in HPR1000 was simulated by using our heat exchanger. The aerosol experiments of two accident sequences were mainly carried out, namely LLOCA (large break loss of coolant accident) and SBO (station blackout) accident. The two accident sequences were calculated by an integrated simulation program to obtain the variation of thermal parameters in the accident sequence. This experiment focused on simulating the change of thermal parameters in the containment to explore the influence of thermal parameters on aerosol deposition behavior. In addition, it focused on the influence of aerosol release form, release time, release rate and other factors on aerosol natural deposition behavior. The consistent law of thermal parameters such as pressure and temperature offsets the influence of thermal parameters on aerosol deposition rate to a certain extent. The release form, release time and release rate of aerosol have great influence on the variation of aerosol concentration. Under the same thermal and hydraulic conditions, the aerosol released by the large break has the fastest deposition rate, while the small break may cause the linear release of the same amount of aerosol with a second deposition time, while the linear aerosol released by the small break has the second longest deposition time, and the exponential aerosol released by other conditions has the longest deposition time. The aerosol concentration will peak for a short period of aerosol release, and then decrease exponentially. Long-term release may cause the containment gas space to remain in a state of high aerosol concentration for a long time, which increases the risk of aerosol release to the outside world through cracks in the containment vessel or pipes. The increase in the initial aerosol concentration will enhance the aerosol coagulation effect, resulting in an increase in the number of large-particle aerosols, which may in turn increase the aerosol removal rate. This study extends the use of the lumped exponential decay model and applies it to the changes in aerosol concentration under transient conditions. The experimental results show that it is still applicable to a certain extent, and further consideration can be given to partitioning calculations for aerosol stratification.